Pengembangan Website Penerimaan Tamu Interaktif Untuk Meningkatkan Layanan di DISPORAPARBUD SERGAI Menggunakan Laravel - Bagus Rizki Lubis; Aninda Muliani (Journal Of Informatics And Busisnes, 2024)
Serdang Bedagai Regency Youth Sports Tourism and Culture Service (DISPORAPABUD) is one of the OPDs in the Serdang Bedagai Regional Government.[1] DISPORAPARBUD needs a website that can help manage the guest book because at this service many guests often come every day from various agencies to various regions to attend meetings, regular meetings, and other matters [2]. This research aims to develop an interactive guest reception website using the Laravel framework to improve services at the agency [3]. This interactive guest reception website is designed to simplify the registration and management process for guests visiting the Youth, Sports, Tourism and Culture Department. Interactive facilities such as online registration forms, current activity information, and online communication mechanisms are integrated on the website to increase guest engagement. Evaluation results show significant improvements in the efficiency of the guest reception process and increased user satisfaction. The use of the Laravel framework provides the system stability and security needed to handle sensitive data. With this website, it is hoped that the Serdang Bedagai Regency Youth, Sports, Tourism and Culture Service can provide better and more responsive services to guest needs, while also improving the agency's image in public services.